Commemorative French coins. Engraving. - Auteur inconnu (Wikimedia Commons)
Notice iconographique issue de Wikimedia Commons. Titre: Commemorative French coins. Engraving.. Commemorative French coins. Engraving. Iconographic Collections
Licence Creative Commons Attribution 4.0 via Wikimedia Commons
Keywords: iconographie; illustration; gravure; patrimoine; wikimedia commons